Increased Susceptibility of Rainbow Trout to Infectious Hematopoietic Necrosis Virus After Exposure to Copper - Hetrick, Frank M. (1979)
Exposure of rainbow trout to sublethal levels of copper in water increased their susceptibility to infectious hematopoietic necrosis virus. In most instances, the percent mortality was twice as great in the stressed groups compared with those groups which were not stressed but received the same virus dose. Although the level of copper in the water influenced the mortality rates, the length of exposure did not prove to be critical, as similar results were obtained after 1, 3, 5, 7, or 9 days of exposure. When different virus challenges were employed, the percent mortalities were again greater in the stressed fish at all virus doses tested, and at one dose level mortalities were noted in the stressed group but not in the untreated group.